ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN TENAGA LISTRIK KONSUMEN RUMAH TANGGA KECIL PT PERUSAHAAN LISTRIK NEGARA (PERSERO) - Assagaf, Aminullah (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2010)
This research is analysis of electricity demand, and focus for small recidence sector in PT Perusahaan listrik Negara (Persero) or PT PLN (Persero). Dependent variable is demand electricity or kWh sales, and independent variable consist of install capacity, average tariff, and rate of capacity using percustomers. Step of research and process result based on SPSS calculation, and use cross section data on January 2010. Obtain result that install capacity and rate of capacity using percustomers has given positif impact, and average tariff has given negative impact. Install capacity variable has significant influence to electricity demand of small recidence sector, but average tariff and rate of capacity using percustomers has not significant influence to electricity demand of small recidence sector. PLN’s management has to observe growth of explanatory variable to make policy for demand and supply equilibrium and toward customers satisfaction.Keyword : Electricity demand, Strategy Management, and Microeconomic